Experimental study on elastic-plastic behavior of high-strength steel beam-to-column panel zone considering under-matching welding effect. (15th September 2022) - Luo, Pengjun; Tanaka, Tsuyoshi; Asada, Hayato
Highlights: Eight beam-to-column cruciform joint specimens made of H-SA700B high strength steels are tested under cyclic loading. The effect of welding condition on elastic-plastic behavior of panel zones formed by different column cross-sections is investigated. The under-matching welding has negligible effect on the shear strength of panel zones formed by the built-up cross-sections. The under-matching welding results in significant shear strength reduction for panel zones formed by cold-formed cross-sections. Abstract: This paper presents an experimental study on the elastic-plastic behavior of high-strength steel beam-to-column panel zones with the columns being formed by matching or under-matching welding conditions. Four column cross-sections, including built-up H-shape, built-up box-shape, cold-formed square, and cold-formed circular, are considered. The test involves eight beam-to-column joints subjected to cyclic loading with lateral displacements imposed at the beam ends. The failure modes, hysteretic curves, shear strengths, and shear strain distributions of panel zones are discussed. The test results indicated that all the specimens showed the linear elastic behaviors until the panel shear yield deformation angle and the panel zones exhibited stable hysteretic behavior even for large shear deformations. Regardless of welding conditions, the panel zones formed by built-up box-shape columns have the highest shear strength and initial stiffness among the four column types. The failure modes of specimens composed of built-up box-shape or cold-formed square columns were dependent on the welding conditions. In addition, the welding condition has negligible effect on the shear strength of panel zones formed by built-up H-shape or built-up box-shape columns; whereas, comparing to the matching welding, the under-matching welding resulted in a strength decreasing of about 8.96–12.67% for the panel zones formed by cold-formed square and cold-formed circular pipes.